Mechanical strain induces involution-associated events in mammary epithelial cells - Quaglino, A. (2009)
Background: Shortly after weaning, a complex multi-step process that leads to massive epithelial apoptosis is triggered by tissue local factors in the mouse mammary gland. Several reports have demonstrated the relevance of mechanical stress to induce adaptive responses in different cell types. Interestingly, these signaling pathways also participate in mammary gland involution. Then, it has been suggested that cell stretching caused by milk accumulation after weaning might be the first stimulus that initiates the complete remodeling of the mammary gland. However, no previous report has demonstrated the impact of mechanical stress on mammary cell physiology. To address this issue, we have designed a new practical device that allowed us to evaluate the effects of radial stretching on mammary epithelial cells in culture. Results: We have designed and built a new device to analyze the biological consequences of applying mechanical stress to cells cultured on flexible silicone membranes. Subsequently, a geometrical model that predicted the percentage of radial strain applied to the elastic substrate was developed. By microscopic image analysis, the adjustment of these calculations to the actual strain exerted on the attached cells was verified. The studies described herein were all performed in the HC11 non-tumorigenic mammary epithelial cell line, which was originated from a pregnant BALB/c mouse. In these cells, as previously observed in other tissue types, mechanical stress induced ERK1/2 phosphorylation and c-Fos mRNA and protein expression. In addition, we found that mammary cell stretching triggered involution associated cellular events as Leukemia Inhibitory Factor (LIF) expression induction, STAT3 activation and AKT phosphorylation inhibition. Conclusion: Here, we show for the first time, that mechanical strain is able to induce weaning-associated events in cultured mammary epithelial cells. These results were obtained using a new practical and affordable device specifically designed for such a purpose. We believe that our results indicate the relevance of mechanical stress among the early post-lactation events that lead to mammary gland involution. © 2009 Quaglino et al., licensee BioMed Central Ltd.